Self Disclosure dengan Resiliensi pada Remaja Wanita di Panti Asuhan - Risa Kristianti; Wahyuni Kristinawati (Jurnal Ilmiah Psyche, 2021)
Teenagers who live in orphanages, especially female adolescents, have different aptitudes from boys to survive in adversity and bounce back from adversity. This has resulted in female adolescents in orphanages needing to have good resilience in order to be able to survive in difficult conditions. An important factor that affects resilience is trust. A sign of trust shown by someone is doing self-disclosure. This study uses quantitative methods to determine the relationship between self-disclosure and resilience in female adolescents in orphanages. The population in this study were female adolescents aged 15-18 years who lived in an orphanage. The sampling technique used is purposive sampling with a total sample of 51 adolescents. The measuring instruments of this research include the Self-disclosure Scale and the Resilience Scale. Based on the results of research conducted using the Pearson Product Moment Correlation technique, it shows a correlation coefficient of 0.617 with p = 0.000 (p <0.05), which means that there is a significant positive relationship between self-disclosure and resilience in female adolescents in orphanages.